2020
DOI: 10.3390/info11080379
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Conversation about Responses to Information Overload

Abstract: In this study, information overload is viewed through the lenses of Library & Information Science and Communication Theory in order to offer recommended solutions for individuals experiencing overload. The purpose of this research was to apply LIS and COMM theories to the pathologies and symptoms of information overload as experienced by individuals in an increasingly digital world. Extant survey work was reviewed and updated with literature collected through limited keyword searches. The authors framed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Notably, others who have applied the Bawden and Robinson (2009) definition of information overload to digital contexts have called for refinement in terms. Lehman and Miller (2020) explained that "overload has been used as a catch-all for individual problems with levels of information." They have suggested that various terms, which "categorize the contexts in which individuals struggle with information," including digital overload, be more solidly defined and adopted (Lehman and Miller 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, others who have applied the Bawden and Robinson (2009) definition of information overload to digital contexts have called for refinement in terms. Lehman and Miller (2020) explained that "overload has been used as a catch-all for individual problems with levels of information." They have suggested that various terms, which "categorize the contexts in which individuals struggle with information," including digital overload, be more solidly defined and adopted (Lehman and Miller 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lehman and Miller (2020) explained that "overload has been used as a catch-all for individual problems with levels of information." They have suggested that various terms, which "categorize the contexts in which individuals struggle with information," including digital overload, be more solidly defined and adopted (Lehman and Miller 2020). Importantly, this study suggests that generational differences be considered in the process of revising the definition of digital overload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these attributes, learning is assumed to be foundational (Heeks & Ospina, 2018). As highlighted by other scholars, it implies users' active engagement which initiates critical thinking (McDougall, 2019;Lehman & Miller, 2020). Resilient information systems do not exclude the potential of information overload a priori.…”
Section: User Media Literacy and Resilient Information Systemsmentioning
confidence: 99%
“…Further, Guess et al (2020) emphasize that discernment between false and accurate news can be increased by "teaching people more effective heuristics" instead of relying on quicker, cost-sensitive measures (Thirumuruganathan et al, 2021) which require users to pay attention to the assessment of singular posts. Lehman and Miller (2020) also note that active engagement (in their case microblogging) increases learning effects of individuals. In case users find interaction "simple, fun and educational" (Micallef et al, 2021), they are ready to invest time and increase their media literacy.…”
Section: Suitability Of Existing Approachesmentioning
confidence: 99%